In vitro evaluation of silver-zinc oxide-eugenol nanocomposite for enhanced antimicrobial and wound healing applications in diabetic conditions - Hari Prasath Nagaiah; Malik Basha Samsudeen; Akshaya Rani Augustus; Karutha Pandian Shunmugiah (Discover Nano)
Abstract Diabetic wounds with chronic infections present a significant challenge, exacerbated by the growing issue of antimicrobial resistance, which often leads to delayed healing and increased morbidity. This study introduces a novel silver-zinc oxide-eugenol (Ag+ZnO+EU) nanocomposite, specifically designed to enhance antimicrobial activity and promote wound healing. The nanocomposite was thoroughly characterized using advanced analytical techniques, confirming its nanoscale structure, stability and chemical composition. The Ag+ZnO+EU nanocomposite demonstrated potent antimicrobial efficacy against a range of wound associated pathogens, including standard and clinical isolates of Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans. Minimum inhibitory concentrations of Ag+ZnO+EU for standard and clinical isolates were significantly lower than those of the individual components, highlighting the synergistic effect of the nanocomposite. Time-kill assays revealed rapid microbial eradication, achieving complete sterility within 240-min. Importantly, the nanocomposite effectively eliminated persister-like cells, which are typically resistant to conventional treatments, suggesting a potential solution for persistent infections. In vitro scratch assays using human keratinocyte cells demonstrated that the Ag+ZnO+EU nanocomposite significantly accelerated wound closure, with near-complete healing observed within 24-h, indicating enhanced cell migration and tissue regeneration. Additionally, the nanocomposite showed potential antidiabetic effects by increasing glucose uptake up to 97.21% in an in vitro assay using 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl) amino]-2-deoxy-D-glucose, a fluorescent glucose analog, suggesting potential applications beyond wound healing. These findings highlight the Ag+ZnO+EU nanocomposite as a promising candidate for addressing both antimicrobial resistance and impaired wound healing in diabetic contexts. Graphical Abstract